Emerging reservoir delta‐backwaters: biophysical dynamics and riparian biodiversity. Issue 3 (19th March 2019) - Volke, Malia A.; Johnson, W. Carter; Dixon, Mark D.; Scott, Michael L.
Abstract: Deltas and backwater‐affected bottomlands are forming along tributary and mainstem confluences in reservoirs worldwide. Emergence of prograding deltas, along with related upstream hydrogeomorphic changes to river bottomlands in the backwater fluctuation zones of reservoirs, signals the development of new and dynamic riparian and wetland habitats. This study was conducted along the regulated Missouri River, USA, to examine delta‐backwater formation and describe vegetation response to its development and dynamics. Our research focused specifically on the delta‐backwater forming at the confluence of the White River tributary and Lake Francis Case reservoir. Objectives of the research were to: (1) describe and analyze the process of delta‐backwater formation over space and time; (2) determine by field sampling and GIS mapping how vegetation has responded to development of the delta‐backwater; and (3) compare the woody plant communities of the delta‐backwater to those along free‐flowing and regulated remnant river reaches. In response to base level changes caused by reservoir filling, the thalweg of the lower 31 km of the original White River channel and adjacent floodplain aggraded by up to 12 m between 1954 and 2011. The overall channel slope flattened from 0.70 to 0.29 m/km. Riparian Populus – Salix forests increased in area by nearly 50% during the post‐dam period by colonizing new deltaic and floodplain deposits. Many of the native woody species found along natural and regulated river reaches were also found on the delta‐backwater. Woody species sorted along a fluvial to delta gradient; wetland affiliated species ( Salix spp., Typha spp.) dominated the delta‐backwater near the reservoir while riparian species ( Populus, Fraxinus ) dominated in upstream portions of the delta‐backwater. This habitat complex supports young stands of native riparian vegetation now in decline in remnant reaches protected from flooding.